1993
DOI: 10.1111/j.1365-2796.1993.tb00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered adrenocorticotropin and Cortisol secretion in abdominal obesity: implications for the insulin resistance syndrome

Abstract: Abdominal obesity may be associated with subtle central adrenal insufficiency, which might also affect insulin and lipoprotein metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 32 publications
6
51
1
Order By: Relevance
“…[17][18][19] This is further supported by evidences showing that the HPA axis responsiveness to stimuli such as acute stress, CRH/AVP, 20 adrenergic manipulations, 21 hypoglycemia, or a standard meal 22,23 is enhanced in idiopathic obesity, particularly in visceral obesity. 21 The mild increase in glucocorticoid production and exaggerated cortisol responses in obesity can be explained by increased forward drive to the HPA axis, 24 and/or by reduced sensitivity to HPA axis feedback.…”
Section: Glucocorticoids and Neuropeptide Ymentioning
confidence: 70%
“…[17][18][19] This is further supported by evidences showing that the HPA axis responsiveness to stimuli such as acute stress, CRH/AVP, 20 adrenergic manipulations, 21 hypoglycemia, or a standard meal 22,23 is enhanced in idiopathic obesity, particularly in visceral obesity. 21 The mild increase in glucocorticoid production and exaggerated cortisol responses in obesity can be explained by increased forward drive to the HPA axis, 24 and/or by reduced sensitivity to HPA axis feedback.…”
Section: Glucocorticoids and Neuropeptide Ymentioning
confidence: 70%
“…In a study of 66 adult males aged 30 to 55 years, Hautanen et al reported a correlation between the cortisol response to IV ACTH and the subject's waist-hip ratio (51). It has been suggested that adrenal secretion of cortisol in response to ACTH may be blunted due to hyperinsulinemia (124).…”
Section: Ivacthmentioning
confidence: 99%
“…Some authors have observed central adrenal insufficiency with concurrent disorders of insulin and lipoprotein metabolism in this group [9]. Others have reported that both ACTH and cortisol concentration may be increased [10,11].…”
Section: Discussionmentioning
confidence: 99%